"Essentials" for Worship: Evelyn Underhill's Prayer Book. (September 2021) - Wrigley-Carr, Robyn
This article explores some of the theological principles required for effective church worship. In 1927, Evelyn Underhill (1875–1941) outlined four "Essentials" or principles for effective liturgy, identified in the context of revisions to the Anglican Book of Common Prayer : adoration, the historic, the Eternal, and the interplay between spirit and sense. This article explores the extent to which these four theological principles are actually embodied in prayers that Underhill selected and wrote for retreat leading at The House of Retreat, Pleshey (north London, UK), recently published as Evelyn Underhill's Prayer Book . Additional theological principles, not mentioned in Underhill's "Essentials" essay but evident in her book of prayers, are also evaluated and exemplified. Underhill's guidance to her spiritual directees about the value of liturgy in their spiritual lives is also briefly touched upon.